Exploring the Dynamics of Innovation Antecedents and Outcomes in Business Performance - Aristayudha, A A Ngurah Bagus; Widnyani, Ni Made; Rettobjaan, Vitalia Fina Carla; Richadinata, Kadek Riyan Putra (Journal of Economics and Public Health, 2024)
The current research critically addresses a significant gap in understanding the intricate dynamics between the drivers and outcomes of innovation within various organizational contexts. While innovation is widely recognized as a crucial driver for growth and competitiveness in the rapidly evolving business landscape, the specific mechanisms through which these drivers influence outcomes remain underexplored. This lack of detailed insight is a substantial barrier to effective strategy development and implementation, underscoring the importance of this study. The research aims to thoroughly explore key antecedents such as organizational culture, leadership, financial strategies, and external environmental conditions that promote an innovative environment. It also evaluates the extensive impact of these innovations on business performance, focusing particularly on market competitiveness, operational efficiency, and customer loyalty. By examining the connections between these factors, the study seeks to outline the pathways through which innovation enhances business performance across various industries and market conditions. The formulated research questions are designed to identify the principal antecedents of innovation, assess their broad impacts on business metrics, and ascertain under which circumstances these effects are maximized. This comprehensive analysis intends to bridge the theoretical and empirical gaps, providing insights that could guide both academic research and practical business strategy development in the realm of innovation management.